Esophageal length in children: Reference data and a novel predictive equation. Issue 3 (25th November 2021) - Tinawi, Georges K.; Stringer, Mark D.
Abstract: Minimal information exists on the length of the child's esophagus, namely the distance from the cricopharyngeus to the esophagogastric junction (EGJ). We aimed to investigate the relationship between esophageal length (EL) and the age, height, and weight of the child. Children undergoing upper gastrointestinal endoscopy between February 2019 and May 2021 at our institution were prospectively audited. Children with anatomical esophageal disorders were excluded. Endoscopic distances from the incisors to the cricopharyngeus and EGJ were obtained, and novel predictive equations derived to predict EL. Intra‐observer agreement for endoscopic measurements showed an intra‐class correlation coefficient of 0.99. A total of 290 children aged 0.4–17.3 years were included in the analysis; they were divided into a model development cohort ( n  = 261) and a model validation cohort ( n  = 29). Measured EL correlated best with height ( r  = 0.92) as compared to age ( r  = 0.90) or weight ( r  = 0.83). The optimal equation for predicting EL was 0.156 × height (cm) – 1.336 (adjusted R 2  = 0.841); this had a success rate of 76% in the validation cohort. The optimal equation for predicting distance from incisors to EGJ was 0.199 × height (cm) + 6.470 (adjusted R 2  = 0.889); this had a success rate of 69% in the validation cohort. This is the first study to report a predictive equation for estimating esophageal length in children. Accurate prediction of esophageal length may assist with clinical esophageal procedures in children such as nasogastric and pH probe placement.